Nitric Oxide-Releasing S-Nitrosothiol-Modified Xerogels - Riccio, Daniel A. (2009)
The synthesis, material characterization, and in vitro biocompatibility of S-nitrosothiol (RSNO)-modified xerogels is described. Thiol-functionalized xerogel films were formed by hydrolysis and co-condensation of 3-mercaptopropyltrimethoxysilane (MPTMS) and methyltrimethoxysilane (MTMOS) sol-gel precursors at varying concentrations. Subsequent thiol nitrosation via acidified nitrite produced RSNO-modified xerogels capable of generating nitric oxide (NO) for up to 2 weeks under physiological conditions. Xerogels also exhibited NO generation upon irradiation with broad-spectrum light or exposure to copper, with NO fluxes proportional to wattage and concentration, respectively. Xerogels were capable of storing up to ∼1.31 µmol NO mg(−1), and displayed negligible fragmentation over a 2 week period. Platelet and bacterial adhesion to nitrosated films was reduced compared to non-nitrosated controls, confirming the antithrombotic and antibacterial properties of the NO-releasing materials. Fibroblast cell viability was maintained on the xerogel surfaces illustrating the promise of RSNO-modified xerogels as biomedical device coatings.